KEKERASAN TERHADAP PEREMPUAN DALAM FILM INDONESIA - Rizki Widya Lestari (Kanal: Jurnal Ilmu Komunikasi, 2015)
This study aimed to analyze the depiction of violence experienced by women in the film "7 heart, 7 love, 7 women". These research method used textual analyses to interpret the signs that are produced in a media text are elements of violence experienced by women. The results showed that violence to the women include (a) physical violence, among others: strangling, pulling, injuring a pregnant woman, and rape, (b) symbolic violence, among others: (1) psychological violence: deceive, insult, infidelity; (2) financial violence: lack of accountability husband; (3) functional violence: restrictions on women's social role as executor of reproductive function.